2022
DOI: 10.1039/d2py01018f
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the self-assembly of sparsely grafted amphiphilic copolymers in aqueous solution

Abstract: This review describes the self-assembly of sparsely grafted amphiphilic copolymers and highlights the effects of structural factors and solvents on their self-assembly behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 166 publications
0
11
0
Order By: Relevance
“…In the self-assembly of amphiphilic graft copolymers, the surface area of the hydrophilic region depends on the flexibility ( persistence length; p) of the backbone chain, which forms the hydrophilic domain by folding. 61,66 A longer persistence length results in a more rigid and less flexible chain, while a shorter persistence length results in a more flexible and softer chain. We have reported that the formation of vesicles occurs when the persistence length p of the main chain in graft polymers is <2 nm, rod-shaped aggregates are formed for 2 nm < p < 2.7 nm, and spherical aggregates are formed for p > 2.9 nm.…”
Section: Paper Polymer Chemistrymentioning
confidence: 99%
“…In the self-assembly of amphiphilic graft copolymers, the surface area of the hydrophilic region depends on the flexibility ( persistence length; p) of the backbone chain, which forms the hydrophilic domain by folding. 61,66 A longer persistence length results in a more rigid and less flexible chain, while a shorter persistence length results in a more flexible and softer chain. We have reported that the formation of vesicles occurs when the persistence length p of the main chain in graft polymers is <2 nm, rod-shaped aggregates are formed for 2 nm < p < 2.7 nm, and spherical aggregates are formed for p > 2.9 nm.…”
Section: Paper Polymer Chemistrymentioning
confidence: 99%
“…Different morphologies such as spherical, cylindrical, lamellar and other complicated structures are prepared by bottom-up self-assembly of block copolymers. [1][2][3][4] The selfassemblies are widely studied in biological and materials science. For example, amphiphilic block copolymers are selfassembled into vesicles that are extensively studied in controlled drug delivery and therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis and self assembly of copolymers have been extensively studied [ 21 , 22 , 23 ]. Some scientists designed new molecular structures and synthesized new efficient, green, and low-cost copolymers to improve the efficiency of exfoliate graphite and the stability of graphene dispersion.…”
Section: Introductionmentioning
confidence: 99%